Knowledge, attitude and practices regarding reproductive health among rural and urban adolescent girls - Saxena, Somya; Gupta, Veena; Shweta, Kumari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Menstruation is a biological event imbued with social, cultural and personal significance. Due to impact of social media and internet the incidence of indulging in unprotected sexual intercourse and unplanned pregnancies are rapidly increasing among teenagers. Objectives were to assess the knowledge regarding safe sex and contraceptive methods and compare the menstrual and sexual awareness among adolescent girls in rural and urban settings. Methods: The health questionnaire was prepared from WHO adolescent health manual as reference base. The adolescent survey was done. Results: In present study maximum number of girls had attained menarche between 12-15 years in both groups. The study showed lack of menstrual hygiene among rural girls in compare to urban girls where 79% girls use either sanitary pads or cotton and in comparison to urban girls, rural girls had more restrictions in going out. Conclusions: Education regarding proper physiology of menses and there should be open discussion regarding restrictions and taboos related to menses at the school level to minimise the false beliefs.